The Influence of Attitude and Trust in Green Banking on Customer Interest in Opening an Account: Case Study of PT Bank Central Asia Tbk - Permana, Frianka Bagja; Hidayah, Riski Taufik (The Es Economics and Entrepreneurship, 2025)
This study aims to analyze the factors that influence customer interest in using green banking services, specifically when opening an account at BCA. Using a quantitative approach and the SEM-PLS method with a sample of 385 respondents, the study found that the variables Green Perceived Value, Green Trust, Environmental Concern, Perceived Consumer Effectiveness, Perceived Environmental Integrity, and Collectivism have a significant effect on Green Purchase Intention. Meanwhile, Green Perceived Risk does not show a significant effect. This finding confirms the importance of environmental values and trust in encouraging the adoption of sustainable banking services.